2023
DOI: 10.1021/acs.est.2c09261
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Effects of Late Macroalgal Blooms on Dissolved Inorganic Carbon Pool through Alkalinity Enhancement in Coastal Ocean

Abstract: Taking the world's largest green tide caused by the macroalga Ulva prolifera in the South Yellow Sea as a natural case, it is studied here if macroalgae can perform inorganic carbon sequestration in the ocean. Massive macroalgae released large amounts of organic carbon, most of which were transformed by microorganisms into dissolved inorganic carbon (DIC). Nearshore field investigations showed that, along with seawater deoxygenation and acidification, both DIC and total alkalinity (TAlk) increased significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…To account for conservative mixing of water masses with different salinities on TA and DIC, a normalization scheme against a fixed salinity (nTA and nDIC) (Chen and Millero 1979; Friis et al 2003) is commonly employed to investigate the impacts of metabolic activities on seawater carbonate chemistry (e.g., Courtney et al 2021) or to differentiate metabolic effect from anthropogenic CO 2 signals (Peng et al 1998). Moreover, the slope of nTA–nDIC relationship is also widely used to infer major biogeochemical processes affecting carbonate chemistry in coastal environment (Hunt et al 2022; Szymczycha et al 2023; Xiong et al 2023; Yin et al 2023). This data interpretation method is based on the premise that different biogeochemical processes affect TA and DIC differently (Table 1).…”
Section: Process Formula ∆Ta : ∆Dicmentioning
confidence: 99%
“…To account for conservative mixing of water masses with different salinities on TA and DIC, a normalization scheme against a fixed salinity (nTA and nDIC) (Chen and Millero 1979; Friis et al 2003) is commonly employed to investigate the impacts of metabolic activities on seawater carbonate chemistry (e.g., Courtney et al 2021) or to differentiate metabolic effect from anthropogenic CO 2 signals (Peng et al 1998). Moreover, the slope of nTA–nDIC relationship is also widely used to infer major biogeochemical processes affecting carbonate chemistry in coastal environment (Hunt et al 2022; Szymczycha et al 2023; Xiong et al 2023; Yin et al 2023). This data interpretation method is based on the premise that different biogeochemical processes affect TA and DIC differently (Table 1).…”
Section: Process Formula ∆Ta : ∆Dicmentioning
confidence: 99%
“…Given the massive biomass of these macroalgae, which can reach millions of tons wet weight (Wang et al, 2018;Xing et al, 2018;Bach et al, 2021), their contribution of CDOM is likely to have a substantial impact on regional marine DOM budgets. While the fate of U. prolifera-and Sargassumderived CDOM with respect to microbial degradation has been relatively well studied (e.g., Zhang and Wang, 2017;Chen et al, 2020;Xiong et al, 2023), less attention has been paid to their photochemical degradation. Shank et al (2010b) found that CDOM leached from Sargassum (S-CDOM hereinafter) could be readily photodegraded by simulated solar radiation, losing absorbance and producing CO 2 and CO. Sun et al (2020) reported that both the abundance and molecular weight of U. prolifera-derived CDOM (UP-CDOM hereinafter) decreased under solar irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Macroalgae are the most productive plants in coastal vegetated ecosystems . They have a net primary productivity (NPP) of 1.32 Pg C yr –1 worldwide and contribute significantly to ocean carbon sequestration through pathways such as macroalgal carbon burial in local sediments or long-distance carbon export to deep sea as well as contribution of recalcitrant dissolved organic carbon (RDOC), thus receiving much attention under climate change scenarios. Macroalgal carbon sequestration processes are complex, involving the conversion between different forms of carbon, and are largely regulated by microbial decomposition and photodegradation. For example, microbial degradation of dead macroalgal debris produces different forms of carbon, some of which can be returned to the atmosphere as carbon gas and some can be stored in forms of RDOC, recalcitrant particulate organic carbon (RPOC), and relatively stable dissolved carbonate in the ocean . In addition to dead macroalgal debris, a large amount of organic carbon, including DOC and POC, can be released during macroalgal growth. ,, Microbial carbon pump plays an important role in driving macroalgal DOC from the labile to recalcitrant state, indirectly involving in macroalgal carbon sequestration. , However, the fate of the POC released during macroalgal growth and their carbon sequestration effect are still unclear.…”
Section: Introductionmentioning
confidence: 99%